1998
DOI: 10.1038/sj.ejcn.1600522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish oil supplementation on apolipoprotein B100 production and lipoprotein metabolism in normolipidaemic males

Abstract: Objective: To evaluate the effects of four weeks of ®sh oil supplementation on apolipoprotein B100 production and lipoprotein metabolism in normolipidaemic males. Design and subjects: Very low density lipoprotein (VLDL) apolipoprotein B100 (apoB100) kinetics in ten healthy, white males, aged 22±43 y (mean 32 y) were investigated using a 13 C-leucine technique and gas chromatography-mass spectrometry before and after ®sh oil supplementation. Intervention: All subjects received 10 g (1.8 g EPA, 1.2 g DHA)ad of ®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 16 publications
4
22
0
2
Order By: Relevance
“…Effect of fish oils on apoB metabolism. Animal and human studies have shown that fish oils lower plasma triglycerides by inhibiting hepatic VLDL-apoB secretion (18,20). This finding agrees with our observation that the VLDL-apoB pool size and secretion rate decreased with fish oils.…”
Section: Regulation Of Apolipoprotein B Kineticssupporting
confidence: 92%
See 2 more Smart Citations
“…Effect of fish oils on apoB metabolism. Animal and human studies have shown that fish oils lower plasma triglycerides by inhibiting hepatic VLDL-apoB secretion (18,20). This finding agrees with our observation that the VLDL-apoB pool size and secretion rate decreased with fish oils.…”
Section: Regulation Of Apolipoprotein B Kineticssupporting
confidence: 92%
“…Our pretreatment data were consistent with those from previous kinetics studies. The independent effects of statins (34,35) or fish oils (18,20,36,37) on apoB kinetics have been examined only in nonobese, insulinsensitive subjects. The present study extends previous studies to insulin-resistant subjects.…”
Section: Regulation Of Apolipoprotein B Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first models used to describe VLDL apoB kinetics used a monoexponential function, equivalent to a singlecompartment model, to determine FCR (55)(56)(57). Al-though these models provided a good description of the experimental data, with the exception of the early time points, using such a model to simulate an exogenously labeled VLDL kinetics study would reveal that the apoB tracer curve was monoexponential.…”
Section: Model Simulationmentioning
confidence: 99%
“…At the same time, the conversion of VLDL to LDL was reduced. The effect of fish oil supplements on VLDLapoB-100 kinetics was investigated by Bordin et al (19). Four weeks of feeding fish oil supplements resulted in a decreased production of VLDL-apoB-100 and a decreased triglyceride concentration.…”
Section: Vldl-and Ldl-apob Metabolismmentioning
confidence: 99%